Understanding Relationship between Geographical Science and Geographical Indicator in Business Products (Database Evidence Analysis) - Nofirman, Nofirman (Budapest International Research and Critics University, 2021)
This discussion paper aimed to describe the relationship between understanding Geography and geographic indicators of agricultural products in Indonesia. The author believes that understanding Geography will help business people to understand the many locations and conditions of a production site. Likewise, Geography helps potential consumers of a product with the different locations, conditions, and characteristics of each region in Indonesia so that this understanding facilitates the parties. To discuss the two variables above, we review many geographies literature and business geography indicators from several databases through electronic search assisted by keyword searching. Then our study involved a data coding system, in-depth evaluation, and data retrieval of findings based on the principles of validity and reliability. We designed this study as a qualitative report model—data analysis to serial correlation as interpretation and description. Based on the findings and discussion data, we can conclude that there is a significant correlation between the understanding of Geography and the Geography indicators of the agricultural product business in the country. In other words, the better the understanding of Geography, the easier it is for the parties (businessmen and consumers) in business transactions.